Eyeblink Classical Conditioning in Alcoholism and Fetal Alcohol Spectrum Disorders - Cheng, Dominic T.; Jacobson, Sandra W.; Jacobson, Joseph L.; Molteno, Christopher D.; Stanton, Mark E.; Desmond, John E. (Frontiers in Psychiatry, 2015)
Alcoholism is a debilitating disorder that can take a significant toll on health and professional and personal relationships. Excessive alcohol consumption can have a serious impact on both drinkers and developing fetuses, leading to long-term learning impairments. Decades of research in laboratory animals and humans have demonstrated the value of eyeblink classical conditioning (EBC) as a well-characterized model system to study the neural mechanisms underlying associative learning. Behavioral EBC studies in adults with alcohol use disorders and in children with fetal alcohol spectrum disorders report a clear learning deficit in these two patient populations, suggesting alcohol-related damage to the cerebellum and associated structures. Insight into the neural mechanisms underlying these learning impairments has largely stemmed from laboratory animal studies. In this mini-review, we present and discuss exemplary animal findings and data from patient and neuroimaging studies. An improved understanding of the neural mechanisms underlying learning deficits in EBC related to alcoholism and prenatal alcohol exposure has the potential to advance the diagnoses, treatment, and prevention of these and other pediatric and adult disorders.